1990
DOI: 10.1007/bf00170566
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of cultured Catharanthus roseus cells using a fibreglass substratum

Abstract: Cultured C a t h a r a n t h u s roseus cells were immobilized using geometrically identical needled fibreglass mats prepared with a range of surface coatings. The phenyl (PS), polyglycol (PG), aldehyde (CHO), alkyl (CTMS), and silanol (AW) coatings, along with the untreated glass (HC) surface, produced surfaces with a range of surface tensions. The immobilization efficiency of the substratum, measured as the percentage of cells immobilized, increased with increasing substratum surface tension in the order PS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 19 publications
(34 reference statements)
2
11
0
Order By: Relevance
“…Since the porosities and densities of all these materials were very similar, fungal growth and adhesion to the matrix seemed to have been affected more by the fungal affinity towards the support in relation to the surface tension of the carriers, their free chemical groupings and added adjuvants, than by their physical characteristics alone, as shown previously by Facchini and DiCosmo (1990). The increase in biomass yield observed that was associated with higher sucrose consumption might have been the result of higher carbon assimilation because of better cell oxygenation.…”
Section: R Arrhizus Growth After Immobilisationsupporting
confidence: 55%
“…Since the porosities and densities of all these materials were very similar, fungal growth and adhesion to the matrix seemed to have been affected more by the fungal affinity towards the support in relation to the surface tension of the carriers, their free chemical groupings and added adjuvants, than by their physical characteristics alone, as shown previously by Facchini and DiCosmo (1990). The increase in biomass yield observed that was associated with higher sucrose consumption might have been the result of higher carbon assimilation because of better cell oxygenation.…”
Section: R Arrhizus Growth After Immobilisationsupporting
confidence: 55%
“…Few immobilized systems have been used in the production step because secondary meta- [108] C. roseus [69,109] M. pruriens [110] Reticulate polyurethane matrix C. frutescens [111] D. deltoidea [112] Ceramic hollow fiber C. roseus [48] Polyester fiber matrix C. roseus [113] N. tabacum Soybean Surface-coated fiberglass C. roseus [114] bolites are generally intracellular in nature, however, they have been used with success in biotransformations. Alfermann et al were able to convert fl-methyldigitoxin to digoxin using D. lanata immobilized in Ca-alginate beads [115].…”
Section: Process Systemsmentioning
confidence: 99%
“…In the first stage, cells are spontaneously attracted to the support surface due to van der Waal's forces, aided by entrapment of ceils in pores or other irregularities on the surface of the support (Facchini & DiCosmo 1990, Facchini et al 1989). Subsequently, plant cells appear to secret a mucilaginous substance of some sort, thereby firmly cementing themselves to the support surface (Archambault et al 1989;Rhodes et al 1985;Robins et al 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The development of Facchini-DiCosmo surface immobilization technology has been described in a succession of published articles (DiCosmo et al 1988;Facchini et al 1988a, b;Facchini et al 1989;Facchini & DiCosmo 1990, 1991a. Considerable insight into the theoretical and thermodynamic aspects of plant cell immobilization on polymer surfaces has also been gained.…”
Section: Facchini-dicosmo Surface Immobilization Technologymentioning
confidence: 99%
See 1 more Smart Citation